Analysis of wind speed characteristics using different distribution models in Medan City, Indonesia - Suwarno Suwarno; Ismail Yusuf; M. Irwanto; Ayong Hiendro (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Estimating wind speed characteristics plays an essential role in designing a wind power plant at a selected location. In this study, the Weibull, gamma, and exponential distribution models were proposed to estimate and analyze the wind speed parameters and distribution functions. Real measured data were collected from Medan City, Indonesia. The scale and shape factors of wind distribution for three years data were calculated. The observed cumulative probability of the three models was compared to predicted wind characteristics. The probability density function (PDF) and the cumulative density function (CDF) of wind speed were also analyzed. The results showed that the Weibull model was the best model to determine PDF, while the exponential model was the best model to determine CDF for the Medan City wind site.